THE EFFECT OF SCIENTIFIC INQUIRY LEARNING MODEL USING ON STUDENT’S CONCEPT KNOWLEDGE, AND SCIENCE PROCESS SKILLS IN SENIOR HIGH SCHOOL - Evy Maria Br Meliala; Eva Marlina Ginting; Nurdin Siregar (Jurnal Pendidikan Fisika, 2019)
Study aimed to analyze the effect of scientific inquiry learning model on concept knowledge and science process skills in senior high school students. This research is a quasi experimental research with two group pre-test post-test design. The population of this research is all student of class XI MIA SMAN 1 Delitua (Senior High School), semester I academic year 2018/2019. Selection of sample is done by cluster random sampling that is XI MIA-1 as experiment class applied scientific inquiry learning and XI MIA-2 as control class applied conventional learning. Instrument used in this research is instrument of concept knowledge in essay form as much as 10 problem and instrument of science process skills in essay form as much as 10 problem which have been declared valid by expert team. Form the result of the study concluded that the concept knowledge of students applying scientific inquiry model better than the student’s concept knowledge with conventional learning and the science process skills of students applying scientific inquiry learning model is better than student’s science process skill with conventional learning